Pembimbingan Usaha Ternak Ayam Broiler Di Desa Panjatan, Kecamatan Karanganyar, Kabupaten Kebumen - Eka Wijiasih, Nazla; Satriyo Nugroho, Iwan; Kumala Dewi, Nurlaela (Abditek Nusantara, 2025)
This Community Service (PKM) aims to improve the efficiency, profitability, and sustainability of broiler chicken farming businesses in Panjatan Village, Karanganyar District, Kebumen Regency, thru an integrated mentoring model that incorporates technical, managerial, and marketing aspects. This region has high livestock potential, but small-scale farmers face various constraints, such as inefficient feed management, poor barn sanitation, minimal biosecurity, and dependence on middlemen. Using a three-month (July–September 2025) collaborative action participatory approach, this PKM involves 20 farmers, with the main case study focusing on Mr. Misno's business. Data collection methods include participatory observation, semi-structured interviews, direct training, and quantitative documentation of performance indicators (mortality, FCR, profit). The results show that the intervention successfully reduced mortality from 12–15% to 6% thru improved ventilation, adjusting the temperature according to the age of the chickens, and implementing a complete vaccination schedule (ND, ND-IB, IBD). Feed efficiency increased thru scheduled feeding (8 hours/day) and the substitution of local ingredients (bran, tofu dregs), reducing feed costs by up to 15%. On the marketing side, direct partnerships were established with five food stalls and one chicken slaughterhouse at a fixed contract price of Rp23,000/kg, increasing profit margins by 22%. The main innovation of this PKM lies in three-dimensional integration: (1) agricultural waste-based feed technology, (2) digital business recording via Google Forms, and (3) institutional strengthening thru the formation of an Integrated Livestock Business Group (KUTT). This holistic approach addresses previous research gaps in the southern Kebumen region and provides a contextual, sustainable, and replicable empowerment model for small-scale farmers in remote areas